2002
DOI: 10.1017/s0967199402002253
|View full text |Cite
|
Sign up to set email alerts
|

Impact of adding 5.5 mM glucose to SOF medium on the development, metabolism and quality of in vitro produced bovine embryos from the morula to the blastocyst stage

Abstract: Although toxic for early stages of embryo development, glucose is a physiological metabolic substrate at the morula and blastocyst stages. We evaluated the effect of adding 5.5 mM glucose from the morula stage on bovine blastocyst development and quality. In vitro matured and fertilised bovine oocytes were cultured in modified Synthetic Oviduct Fluid medium containing 5% fetal calf serum, but without added glucose, up to day 5 post-insemination (pi). Morulae were selected and further cultured in the presence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 70 publications
0
8
0
Order By: Relevance
“…Hardy et al described the measurement of pyruvate uptake before embryo transfer as a valuable new criterion for the selection of viable embryos that reached blastocyst stage. They observed that the pyruvate uptake in arrested embryos was significantly lower than for those embryos which developed to the blastocyst stage (66,67). However, to date whether the human embryo OC varies during early preimplantation development has been unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Hardy et al described the measurement of pyruvate uptake before embryo transfer as a valuable new criterion for the selection of viable embryos that reached blastocyst stage. They observed that the pyruvate uptake in arrested embryos was significantly lower than for those embryos which developed to the blastocyst stage (66,67). However, to date whether the human embryo OC varies during early preimplantation development has been unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Starting at the 8-16 cell stage, glucose metabolism rapidly increases as a result of the development of the glycolytic pathway [13]. Although adding 1.5 mM glucose after 48 h postfertilization has been shown to have a beneficial effect on embryo development [18], adding 5.5 mM glucose from the morula stage had only a small effect on the rate of blastulation and quality [14]. In this study, when the glucose concentration was increased from 1.5 to 3 mM at the morula stage, the rate of blastulation at day 7 after fertilization was lower than that obtained with 1.5 mM glucose.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro production of embryos Embryos were produced as previously described by Donnay et al (2002). Briefly, immature cumulusoocyte complexes (COCs) were obtained by aspirating follicles of from 2 to 8 mm from the ovaries of slaughtered cows.…”
Section: General Proceduresmentioning
confidence: 99%